Inhibitory effects of arylcoumarin derivatives on Bacteroides fragilis D-lactate dehydrogenase - Ugurel, Erennur; Danis, Ozkan; Mutlu, Ozal; Yuce-Dursun, Basak; Gunduz, Cihan; Turgut-Balik, Dilek (ELSEVIER, 2019)
Bacteroides fragilis is an anaerobic bacterium naturally hosted in the human colon flora. B. fragilis D-lactate dehydrogenase (BfD-LDH) is an important enzyme which catalyzes the conversion of D-lactate to pyruvate and regulates anaerobic glycolysis. In this study BfD-LDH has been targeted for structure based drug design. B. fragilis D-lactate dehydrogenase has been expressed, purified and inhibitory activities of 25 coumarin derivatives previously synthetize for their antioxidant activity were evaluated. Among the 25 coumarin derivatives, compound 6a, 51, and 6b exhibited the highest inhibitory activity with IC50 values of 0,47 mu M, 0,57 mu M ye 0,057 mu M, respectively. The results indicate that the mechanism by which 6a, 51 and 6b coumarin derivatives inhibit BfD-LDH by reversible non-competitive inhibition. Docking experiments were carried out to further explain the results and compare the theoretical and experimental affinity of these compounds to the BfD-LDH protein. According to docking results, all coumarins bind to the site occupied by pyruvate and the nicotinamide ring of NADH. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Antibiotic resistance; Bacteroides fragilis; Colon cancer; Coumarin; D-Lactate dehydrogenase; Enzyme inhibition; Structure based drug design; COUMARINS; BAD; Biochemistry & Molecular Biology; Chemistry; Polymer Science